COVID-19 pandemic’s disproportionate impact on childhood bereavement for youth of color: Reflections and recommendations - Burns, Michaeleen; Landry, Laura; Mills, David; Carlson, Nichole; Blueford, Jillian M.; Talmi, Ayelet (Frontiers in Pediatrics, 2023)
The COVID-19 pandemic devastated public welfare worldwide, bringing excess deaths connected to causes such as homicide, substance abuse, and heart disease. In the U.S., these mortality increases disproportionally impacted communities of color and contributed to a rise in bereavement among adults and children. The death of an important person is one of the most frequently reported disruptive childhood experiences. According to 2023 Childhood Bereavement Estimation Model (CBEM) results, one in 14 U.S. children will experience the death of a parent by age 18. The current study analyzes the impact of the pandemic on childhood bereavement due to parent death by comparing CBEM results for 2021 and 2020 to the average of annual results for 2016 through 2019 for combined U.S. Census race and Hispanic origin categories. Analyses demonstrate that more than 700,000 U.S. children were newly bereaved due to a parent’s death in 2020 and 2021. 2020 increases were observed for each race and Hispanic origin population, ranging from 14.9% to 72.4% compared to the 2016-2019 annual average. Hispanic Asian Pacific Islander and Hispanic Black youth experienced the largest percentage increases, while non-Hispanic white youth experienced the smallest. The results contribute to the growing evidence documenting longstanding and enduring disparities in critical U.S. health outcomes based on race and Hispanic origin. Recommendations for the scale and focus of efforts to understand and address bereavement in a way that accommodates the rising need for support in diverse populations to help all bereaved children find hope and healing are offered.